PEMANFAATAN INTERNET OLEH MAHASISWA JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 142-146 . Edno Kamelta (CIVED, 2013)
This research is descriptive with population is students of civil engineering amounted to 613 students. By using stratified random sampling, samples are acquired as much as 86 students. Instrument in this research is questionnaire with Likert scaled. This research is purposed to get a description or to reveal the utilization of internet by civil engineering students in engineering faculty of Padang University. In connection to the purpose, data is analyzed by percentage (%) calculation technique. Results in this research shows that internet utilization by civil engineering students highly varied, depend on needs of each student of civil engineering major, engineering faculty of Padang University. Key words : Internet utilization